Upping the Ante of Text Complexity in the Common Core State Standards: Examining Its Potential Impact on Young Readers. (January 2013) - Hiebert, Elfrieda H.; Mesmer, Heidi Anne E.
The Common Core Standards for the English Language Arts (CCSS) provide explicit guidelines matching grade-level bands (e.g., 2–3, 4–5) with targeted text complexity levels. The CCSS staircase accelerates text expectations for students across Grades 2–12 in order to close a gap in the complexity of texts typically used in high school and those of college and career. The first step of the band at second and third grades is examined because it marks the entry into the staircase and a critical developmental juncture. In this article, we examine the theoretical and empirical support for three assumptions that underlie the acceleration of text complexity in Grades 2–3. Then we identify patterns in American reading achievement and instruction to illustrate the potential and far-reaching consequences of an increase in the first step of the CCSS staircase.